Pelayanan Pendidikan Sekolah Dasar dan Pemetaan Potensi Desa Karangduwet - Ernaningsih, Zeny (Jurnal Atma Inovasia, 2021)
Community service activities took place in Karangduwet Village, Paliyan, Gunung Kidul, Yogyakarta. Karangduwet village has a variety of village potentials, but the education of the villagers is still low. Therefore, with various discussions and sources, the researchers decided to choose The Textbook and Mapping of Village Potentials as a project that we will develop with the aim of applying understanding of the basic education system and providing an understanding of the potential that can be developed for the people of Karangduwet Village. Data collection techniques used are documentation studies, namely conducting data studies from various sources related to Karangduwet Village. The first result is textbook, that helps for elementary school students who are expected to be able to provide basic introductions that exist in themselves and in the surrounding environment. The result of the village potential mapping work is to provide innovations in various processed products from agricultural potentials as well as the development of Riyaya Kabudayaan Karangduwet.